Online and on the picket line: West Virginia teachers’ use of an online community to organize - Howell, Crystal D.; Schmitzer, Caleb (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
Teacher organizing in the twenty-first century presents new and as-yet unstudied challenges and opportunities for union leaders and members. In this article, we explore the structure and function of the secret Facebook group created and used by teachers in West Virginia (USA) prior to, during, and since their historic statewide strike in February 2018. Working from poststructuralist and social movement unionist frameworks, we analyze focus group data generated with the group’s admins and moderators as well as survey data collected from the group’s general membership. Together, these data reveal a number of overt and covert group functions, including allowing members to imagine a new good teacher subjectivity. We argue that supporting members as they test such new subjectivities and make their personal, local activism visible within online communities is critical for organizers aiming to nurture collective action among union members, particularly teachers.